(untitled) (Eurasian Research Bulletin, 2023)
For the first time, data are presented confirming the presence in the reef complexes of the Takhtatau molasse formation of organic remains represented by one of the enigmatic groups called paleoaplysins. Despite the problematic origin, these organisms are of interest as active rock formers and indispensable participants in the creation of reef massifs, bioherms, and biostromes. This is extremely important to reflect the high scientific accuracy in the construction of a series of geological maps of the new generation